(untitled) (Research, Society and Development, 2022)
Musculoskeletal symptoms constitute one of the main causes that keep workers away from their occupational activities in Brazil, and generate a direct impact on the quality of life and health of teachers. Given this context, this study was carried out with the objective of identifying the factors associated with musculoskeletal symptoms and the practice of physical activity in elementary school teachers in Campo Grande/MS. A cross-sectional observational study was carried out with 37 teachers from a municipal urban school in Campo Grande/MS, between May and June 2019. A questionnaire was applied to characterize the sample along with the Nordic Questionnaire of Musculoskeletal Symptoms. The associations between the study variables, musculoskeletal symptoms and the practice of physical activity were performed using Fisher’s exact test. The prevalence of musculoskeletal symptoms in the last 12 months was 97.3%, 83.8% in the last seven days and were reasons for absences in 32.4% of the teachers, with the greatest complaint in the lumbar region (78.4%). The male gender was related to greater practice of physical activity (p=0.001), the shortest time of experience (up to 10 years) associated with the greater complaint of musculoskeletal symptoms in the last seven days (p=0.008) and the statutory employment relationship with a greater distance in the last 12 months (p=0.029). It is concluded that basic education teachers have a high prevalence of musculoskeletal symptoms, which causes a high demand for leaves, mainly due to symptoms in the lumbar region, which is associated with shorter experience and statutory employment relationship.